Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Working Life among Nurses at a General Hospital in Malaysia

Abstract: the study was conducted at a General Hospital in Malaysia, focusing on the nurses as the unit of analysis. Job Content, Job Context and Personal Life were parsimoniously selected as the independent variables towards Quality of Working Life (QWL) among nurses at a General in Malaysia. There are there objectives of this study which are to describe the level of QWL among nurses at a General in Malaysia; to identify the relationship between job context, job content and personal life with QWL among nurses, and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The concept of QWL is broad and diverse. In a nutshell, many view QWL as closely linked to job satisfaction, humanizing work or individualizing organizations by assigning jobs that are relevant, giving equal prospects to develop human capabilities so that employees perform well, ensuring job security, covering employees' feelings about the job content, career advancement, autonomy, teamwork, participation in decision-making, communication, adequate pay and benefits, managerial support, work–life balance and providing safe and healthy working conditions (Abdullah et al , 2018; Verma, 2015). Improving the QWL of employees is essential in increasing their performance and productivity.…”
Section: Background Of Study and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of QWL is broad and diverse. In a nutshell, many view QWL as closely linked to job satisfaction, humanizing work or individualizing organizations by assigning jobs that are relevant, giving equal prospects to develop human capabilities so that employees perform well, ensuring job security, covering employees' feelings about the job content, career advancement, autonomy, teamwork, participation in decision-making, communication, adequate pay and benefits, managerial support, work–life balance and providing safe and healthy working conditions (Abdullah et al , 2018; Verma, 2015). Improving the QWL of employees is essential in increasing their performance and productivity.…”
Section: Background Of Study and Hypotheses Developmentmentioning
confidence: 99%
“…With a growing attention in nursing and QWL, it is interesting to note that only limited empirical studies have been conducted on nurses' QWL in Malaysia (Abdullah et al , 2018). In addition to that, studies have shown that the QWL of nurses in Malaysian private hospitals has not been extensively researched.…”
Section: Introductionmentioning
confidence: 99%
“…Person-Job (PJ) Fit and Adaptive Performance (AP) Moreover, it seems that PJ fit is a not important antecedents of Adaptive Performance (Abdullah, Rashid, Lukman, & Annuar, 2018). This aspect only focuses on significant correlation between PJ fit and Adaptive Performance, however, theoretical arguments and results suggested that few psychological and motivational factors mediates the relationship between PJ fit and Adaptive Performance.…”
Section: Literature Review Person-group (Pg) Fit and Adaptive Performance (Ap)mentioning
confidence: 99%
“…The finding of this study will, therefore, be relevant to the ministry of health in Malaysia in making decisions that are relevant to the adaptive performance of nurses (Park, et alm,. 2020;Abdullah, et al,. 2018;Chong, et al,.…”
Section: To the Policy Makers And Other Relevant Stakeholdersmentioning
confidence: 99%
“…In Malaysia, empirical studies regarding QWL among academic staff in universities are still lacking (Farid et al, 2015). Current studies on QWL among academic staff in Malaysia are still restricted and many of them were using quantitative approach (Siron et al, 2012;Narehan et al, 2014;Farid et al, 2015;Ramos et al, 2015;Abdullah et al, 2018). In Malaysia, one of the key focus in the country's Education Blueprint (Higher Education), 2015-2025 is "Talent Excellence", which aims to attract, recruit and retain the best talents among the academic community at the higher education institutes, especially the younger academics.…”
Section: Literature Reviewmentioning
confidence: 99%